Five years later, with double the demographic data, naked mole-rat mortality rates continue to defy Gompertzian laws by not increasing with age - J. Graham Ruby; Megan Smith; Rochelle Buffenstein (GeroScience, 2024)
The naked mole-rat ( Heterocephalus glaber ) is a mouse-sized rodent species, notable for its eusociality and long lifespan. Previously, we reported that demographic aging, i.e., the exponential increase of mortality hazard that accompanies advancing age in mammals and other organisms, does not occur in naked mole-rats (Ruby et al., 2018), a finding that has potential implications for human healthy aging. The demographic data supporting that conclusion had taken over three decades to accumulate, starting with the original rearing of H. glaber in captivity. This finding was controversial since many of the animals in that study were relatively young. In the 5 years following that study, we have doubled our quantity of demographic data. Here, we re-evaluated our prior conclusions in light of these new data and found them to be not only supported but indeed strengthened. We additionally provided insight into the social dynamics of captive H. glaber with data and analyses of body weight and colony size versus mortality. Finally, we provide a phylogenetically proximal comparator in the form of lifespan data from our Damaraland mole-rat ( Fukomys damarensis ) colony and demographic meta-analysis of those data along with published data from Ansell’s mole-rat ( Fukomys anselli ). We found Fukomys mortality hazard to increase gradually with age, an observation with inferences on the evolution of exceptional lifespan among mole-rats and the ecological factors that may have accompanied that evolution.